2021
DOI: 10.12669/pjms.37.3.3897
|View full text |Cite
|
Sign up to set email alerts
|

Determination of serum tumor necrosis factor-alpha (TNF-α) levels in metabolic syndrome patients from Saudi population

Abstract: Objectives: To detect the relationship between serum tumor necrosis factor-alpha (TNF-α) and metabolic syndrome (MetS) components in patients of the Saudi population. Methods: This cross-sectional study was carried out at Jouf University Saudi Arabia from September 2019 to August 2020 and comprised of 183 individuals (91 cases and 92 controls). The blood samples were drawn from the patients visiting two tertiary care settings of Al Jouf province. Biochemical analysis was conducted on various instruments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…Inflammatory markers, such as E-selectin, vascular cell adhesion molecule 1, and CRP, were also indicated to be related to insulin resistance and MetSyn in a study on elderly patients by Ingelsson et al (19). Additionally, Ullah et al reported significantly higher serum levels of TNF-α in participants with MetSyn than in healthy controls (24). Moreover, low-grade inflammation, as indicated through elevated serum inflammatory markers, including CRP and IL-6, is linked to peripheral arterial disease severity and coronary artery disease, as shown by Jacobs et al (20).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inflammatory markers, such as E-selectin, vascular cell adhesion molecule 1, and CRP, were also indicated to be related to insulin resistance and MetSyn in a study on elderly patients by Ingelsson et al (19). Additionally, Ullah et al reported significantly higher serum levels of TNF-α in participants with MetSyn than in healthy controls (24). Moreover, low-grade inflammation, as indicated through elevated serum inflammatory markers, including CRP and IL-6, is linked to peripheral arterial disease severity and coronary artery disease, as shown by Jacobs et al (20).…”
Section: Discussionmentioning
confidence: 97%
“…The sample size of the present study was calculated using a study by Ullah et al (24) and the below formula. Assuming the same number of samples in both groups and with a significance level of α = 0.05 and a power of 1-β = 0.99, the minimum sample size of each study arm was estimated at 74 subjects.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…Various factors are responsible for developing Zn deficiency or can progress to alter the Zn metabolism in liver cirrhosis ( Table 1 ). These factors include insufficient intake alterations in amino acid and protein metabolism, lessened portosystemic shunts, hepatic extraction, impaired absorption due to alcohol influence, and the effects of endotoxins and cytokines, primarily IL-6 [ 63 , 64 ].…”
Section: Deficiency Of Zinc In Liver Diseasesmentioning
confidence: 99%
“…Over the last 25 years, multiple studies reported that fatty tissue hyperplasia and hypertrophy frequently correlated with the negative impact of adipose tissue metabolic equilibrium [100,101]. Additionally, various studies said that tumor necrosis factor-alpha (TNF-α) was significantly raised among obese individuals, eventually rooted in IR, and surfaced the notion of an inflammatory element of obesity [86,[102][103][104][105]. This inflammatory pathological issue is known as "meta-inflammation," a clinical disease of chronic, low-grade inflammation noticed among obese patients [106,107].…”
Section: Obesity and Insulin Resistancementioning
confidence: 99%